PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN: PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Rofik, Mochamad (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2022)
This study aims to determine the motivation variable has a significant effect on work discipline and work motivation has a significant effect on employee performance. The sample in this study were 60 employee respondents who worked at PT. Samitex Bantul. Research analysis using multiple linear regression. The test results show that the work discipline variable has a significant effect on employee performance. It can also be said that every time there is an increase in work discipline, it will affect employee performance. Work motivation variable has an influence on employee performance. That is, every time there is an increase in work motivation will improve employee performance.